Integral Sequence

Calculus Level 3

0 i 2 π e x 2 ( 2 e x ) d x + 0 i 2 π e 2 x 4 ( 2 e x ) d x + 0 i 2 π e 3 x 8 ( 2 e x ) d x + = ? \int_{0}^{i2\pi} \frac{e^{x}}{2(2-e^{x})} \, dx + \int_{0}^{i2\pi} \frac{e^{2x}}{4(2-e^{x})}\, dx+ \int_{0}^{i2\pi} \frac{e^{3x}}{8(2-e^{x})}\, dx +\cdots = \, ?

Clarification : i = 1 i=\sqrt{-1} .


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mateo Reddy
Jun 26, 2016

The sequence can be rewritten as

0 i 2 π 1 2 e x + 1 4 e 2 x + 1 8 e 3 x + . . . 2 e x d x \int_{0}^{i2\pi}\frac{\frac{1}{2}e^{x}+\frac{1}{4}e^{2x}+\frac{1}{8}e^{3x}+...}{2-e^{x}}dx

common ratio = 1 2 e x =\frac{1}{2}e^{x}

S = 1 2 e x 1 1 2 e x = e x 2 e x S_{\infty}=\frac{\frac{1}{2}e^{x}}{1-\frac{1}{2}e^{x}}=\frac{e^{x}}{2-e^{x}}

Now we have the following integral

0 i 2 π e x 2 e x 2 e x d x = 0 i 2 π e x ( 2 e x ) 2 d x \int_{0}^{i2\pi}\frac{\frac{e^{x}}{2-e^{x}}}{2-e^{x}}dx=\int_{0}^{i2\pi}\frac{e^{x}}{(2-e^{x})^{2}}dx

Using u-substitution

u = 2 e x u=2-e^{x}

d u d x = e x \frac{du}{dx}=-e^{x}

d x = 1 e x d u dx=-\frac{1}{e^{x}}du

0 i 2 π e x u 2 × ( 1 e x ) d u = 0 i 2 π 1 u 2 d u = [ 1 u ] 0 i 2 π \int_{0}^{i2\pi}\frac{e^{x}}{u^{2}}\times \left ( -\frac{1}{e^{x}} \right )du=-\int_{0}^{i2\pi}\frac{1}{u^{2}}du=\left [ \frac{1}{u} \right ]_{0}^{i2\pi}

but u = 2 e x u=2-e^{x}

[ 1 2 e x ] 0 i 2 π = 1 2 e i 2 π 1 2 e 0 = 1 1 = 0 \therefore \left [ \frac{1}{2-e^{x}} \right ]_{0}^{i2\pi}=\frac{1}{2-e^{i2\pi}}-\frac{1}{2-e^{0}}=1-1=\mathbf{0}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...